2022
DOI: 10.1186/s40337-021-00519-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a low carbohydrate intake and standard carbohydrate intake on refeeding hypophosphatemia in children and adolescents with anorexia nervosa: a pilot randomised controlled trial

Abstract: Background Nutritional rehabilitation for patients with anorexia nervosa involves balancing the need for weight gain whilst mitigating the risk of refeeding syndrome. Graded caloric increases and restriction of calories from carbohydrate have been used to minimise the risk of developing refeeding hypophosphatemia. There is little evidence to support the recommended nutrient composition, specifically the recommended carbohydrate intake that is safe in this population. The aim of this pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Weight gain did not differ between the two groups because total daily energy intake was similar in both groups. While findings from this trial support the hypothesis that lower carbohydrate nasogastric tube feeding may protect against refeeding hypophosphatemia, they contradict findings from the small RCT showing greater weight gain with higher carbohydrate meal-based refeeding discussed previously [34]. More evidence is needed to understand how macronutrient content and delivery methods (oral vs. enteral) impact the safety and efficacy of refeeding.…”
Section: Route and Methods Of Nutritional Deliverycontrasting
confidence: 64%
See 1 more Smart Citation
“…Weight gain did not differ between the two groups because total daily energy intake was similar in both groups. While findings from this trial support the hypothesis that lower carbohydrate nasogastric tube feeding may protect against refeeding hypophosphatemia, they contradict findings from the small RCT showing greater weight gain with higher carbohydrate meal-based refeeding discussed previously [34]. More evidence is needed to understand how macronutrient content and delivery methods (oral vs. enteral) impact the safety and efficacy of refeeding.…”
Section: Route and Methods Of Nutritional Deliverycontrasting
confidence: 64%
“…This study identified a cut-point of >58.4% carbohydrate as being associated with refeeding hypophosphatemia [33]. A pilot RCT of oral refeeding in children and adolescents with AN and atypical AN assigned patients to meal plans that were either low carbohydrate (<40% total energy from carbohydrate) or standard carbohydrate (50%e60% total energy from carbohydrate) and found that no patients in either group developed refeeding hypophosphatemia in the first seven days of admission but noted greater weight gain with higher carbohydrate feeding [34]. While the investigators concluded that providing 50%e60% of total energy from carbohydrates optimized nutritional rehabilitation without an increasing risk of refeeding hypophosphatemia, these findings should be interpreted with caution given the small sample size and the likelihood that energy intake differed between groups and participants.…”
Section: Macronutrient Distributionmentioning
confidence: 99%
“…In this review, 15 studies looked at weight gain as an outcome; seven compared weight gained in the high-caloric group to that of LCR protocols [ 26 , 35 , 40 , 41 , 43 - 45 ], and eight looked only at the HCR protocol [ 27 , 39 , 47 , 49 - 53 ]. In 11 of these 15 studies, the HCR group's average weekly weight gain was significantly higher than that of the LCR group, ranging from 0.82 kg to 2.7 kg [ 26 , 27 , 40 , 41 , 44 , 46 , 47 , 49 - 52 ]. The most significant weight gain was reported in Garber et al's prospective observational study, which used a quasi-experimental design to compare LCR versus HCR refeeding methods.…”
Section: Reviewmentioning
confidence: 99%
“…Almost 95% of the papers that satisfied our inclusion criteria were published during the last decade, and the majority (80%) were either randomized controlled trials (RCTs) or retrospective studies (cohort and chart reviews). Ten studies compared low-calorie diets to high-calorie diets [26,35,[37][38][39][40][41][42][43][44][45], whereas the remaining studies only looked at high-calorie diets. There was no standard protocol used.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation